SMART STORAGE WITH WEB SERVER INTERFACED - Dharshan, Deepu; S, Supritha; D S, Suma; Kumar, Vinay (International Journal of Research -GRANTHAALAYAH, 2017)
Smart storage with web server interfaced is the new trend which takes leap and puts effort in saving lives. It works by connecting all devices together to give the required stock update. This can be used in many places where stock can’t be updated manually and given to the customers. Our product will make this happen which maintains a healthy relationship between customers, retailers and the production house. It is designed to overcome the present method which we consider to be traditional. Traditional method is the manual updating of stocks which isn’t retailer or consumer friendly. Our product is designed in such a way that the stocks are auto updated with least human interaction.